Reusing larval rearing water and its effect on development and quality of Anopheles arabiensis mosquitoes - Mamai, Wadaka (Malar J, 2016)
BACKGROUND: There is growing interest in applying the sterile insect technique (SIT) against mosquitoes. Mass production of mosquitoes for large-scale releases demands a huge amount of water. Yet, many arid and/or seasonally arid countries face the difficulties of acute water shortage, deterioration of water quality and environmental constraints. The re-use of water to rear successive generations of larvae is attractive as a way to reduce water usage and running costs, and help to make this control method viable. METHODS: To determine whether dirty larval water was a suitable rearing medium for Anopheles arabiensis, in place of the ‘clean’ dechlorinated water routinely used, a series of three experiments was carried out to evaluate the effect of dirty water or mixed clean and dirty water on several parameters of insect quality. Batches of 100 fresh eggs were distributed in dirty water or added to clean water to test the effect of dirty water on egg hatching, whereas first-instar larvae were used to determine the effect on immature development time, pupation, adult emergence, body size, and longevity. Moreover, to assess the effect of dirty water on larval mortality, pupation rate, adult emergence, and longevity, L4 larvae collected after the tilting or larvae/pupae separation events were returned either to the dirty water or added to clean water. RESULTS: Results indicated that reusing dirty water or using a 50:50 mix of clean and dirty water did not affect egg hatching. Moreover, no difference was found in time to pupation, larval mortality or sex ratio when first-instar larvae were added to clean water, dirty water, or a 75:25, 50:50 or 25:75 mix of clean and dirty water and reared until emergence. When late-instar larvae were put back into their own rearing water, there was no effect on pupation rate, emergence rate or female longevity, though male longevity was reduced. When reared from first-instar larvae, however, dirty water decreased pupation rate, emergence rate, body size, and adult longevity. CONCLUSIONS: Re-used larval-rearing water has no impact on egg hatching, development time or mortality of the immature stages of An. arabiensis. However, dirty water is not suitable for the production of high quality adult mosquitoes. Recycling processes to improve water quality and increase insect quality will be investigated, since it may have important implications for the implementation of the SIT in areas where clean water is a scarce or costly resource.